Cephalosporin nitric oxide-donor prodrug DEA-C3D disperses biofilms formed by clinical cystic fibrosis isolates of Pseudomonas aeruginosa. (17th September 2019) - Soren, Odel; Rineh, Ardeshir; Silva, Diogo G; Cai, Yuming; Howlin, Robert P; Allan, Raymond N; Feelisch, Martin; Davies, Jane C; Connett, Gary J; Faust, Saul N; Kelso, Michael J; Webb, Jeremy S
Abstract: Objectives: The cephalosporin nitric oxide (NO)-donor prodrug DEA-C3D ('DiEthylAmin-Cephalosporin-3′-Diazeniumdiolate') has been shown to initiate the dispersal of biofilms formed by the Pseudomonas aeruginosa laboratory strain PAO1. In this study, we investigated whether DEA-C3D disperses biofilms formed by clinical cystic fibrosis (CF) isolates of P. aeruginosa and its effect in combination with two antipseudomonal antibiotics, tobramycin and colistin, in vitro. Methods: β-Lactamase-triggered release of NO from DEA-C3D was confirmed using a gas-phase chemiluminescence detector. MICs for P. aeruginosa clinical isolates were determined using the broth microdilution method. A crystal violet staining technique and confocal laser scanning microscopy were used to evaluate the effects of DEA-C3D on P. aeruginosa biofilms alone and in combination with tobramycin and colistin. Results: DEA-C3D was confirmed to selectively release NO in response to contact with bacterial β-lactamase. Despite lacking direct, cephalosporin/β-lactam-based antibacterial activity, DEA-C3D was able to disperse biofilms formed by three P. aeruginosa clinical isolates. Confocal microscopy revealed that DEA-C3D in combination with tobramycin produces similar reductions in biofilm to DEA-C3D alone, whereas the combination with colistin causes near complete eradication of P. aeruginosa biofilms in vitro . Conclusions: DEA-C3D is effective in dispersing biofilms formed by multiple clinical isolates of P. aeruginosa and could hold promise as a new adjunctive therapy to patients with CF.